Combining Work and Pension in Norway: Gathering Information and Imagining the Future - Grødem, Anne Skevik; Kitterød, Ragni Hege (Nordic Journal of Working Life Studies, 2022)
The Norwegian pension system has provided unprecedented flexibility to combine work and pension drawing from the age of 62, and this has become a popular option. Using qualitative interviews with 28 older workers, we explore their information strategies and motivations. We find that many informants struggle to understand the various options and their consequences and use different strategies to shield themselves from insecurity: they downplay the issue or point to factors beyond their control. Two key motives for early pension take-up are the desire to secure the money for one’s family in the event of early death and to get the money while still vigorous. Informants typically imagine life after 80 as quiet and with fewer material demands. In conclusion, the analysis shows how adaptations to the flexible pension system are embedded in notions of ageing, institutional trust, and a newfound sense of ownership regarding one’s retirement savings.